Progress in Analytical Techniques for Remogliflozin Etabonate, Vildagliptin And Metformin Hydrochloride: A Recently, Approved FDC - Joshi, Prachi; Kotadiya, Rajendra (Current Pharmaceutical Analysis, 2023)
Background: Fixed-dose combinations (FDCs) are renowned formulations that contain two or more drugs pooled in a single dosage form. Their recognition is justified due to several advantages, such as impending therapeutic efficacy, reducing the episodes of adverse drug effects, having pharmacokinetic advantages, reducing pill burden, reducing the dose of individual drugs, and decreasing drug resistance development. Objective: Recently, an FDC tablet of remogliflozin etabonate (100 mg), vildagliptin (50 mg), and metformin HCl (500/1000 mg) has been approved for the treatment of type 2 diabetes mellitus. No analytical method has been reported thus far for this newly approved combination. Methods: Thus, this review collected and simplified information on reported analytical techniques and physicochemical and biological properties for the above-cited FDCs. The authors have explored various authenticated scientific journals, and simplified information was presented to meet the objectives. Results: The reported methods are spectroscopy (40%, 20% & 33%), HPTLC (10%, 14% & 20%), HPLC (50%, 49% & 41%), hyphenated techniques (Nil, 14% & 5%) and electrophoresis methods (Nil, 2% & 1%) for remogliflozin etabonate, vildagliptin and metformin HCl, respectively. Conclusion: Such extensive data would be useful to analysts in developing an analytical method for the analysis of the recently approved FDCs.
Keywords: FDC